The influence of stereotypes about old age on the perception of elderly employees’ labor activity; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Makienko M. A. Marina Alekseevna (2016, 2016)
Title screen